Rated Bomba a content and reception analyses on the representation of female main characters in selected Filipino bombs films in the early 2020s - Jumao-as, Joseph Vincent C.; Luna, Nathalia V.; Tecson, Danicka P. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
This study sought to analyze the representation of female main characters in selected Filipino bombs films in the early 2020s and how Cebuano college-aged-students received these portrayals. Guided by the Feminist Film Theory and Body Politics, the researchers conducted qualitative content analyses on four (4) female main characters to describe their characterization, determine their prominence, treatment, and tone, and analyze if their portrayals are liberating, neutral, or oppressive. The researchers conducted in-depth interviews with nine (9) informants to draw out their perceptions n the female main characters' representation. The date was analyzed through deductive thematic analysis to generate codes and Stuart Hall's Reception Theory to identify the informants' decoding positions. The result of the analyses revealed that the female main characters in Nerisa (2021), Pamasahe (2022), and Bela Luna (2023) were subjected to oppressive representations that perpetuated traditional gender roles and harmful relationship dynamics between men and women. The informants in the liberating perspective conformed to the dominant decoding position as they positively received the representation of the female main characters despite underlying patriarchal undertones while the informants in the oppressive perspective adhered to the oppositional decoding as they negatively received the representations of the female main characters.